141k views
2 votes
Pls hurry the answer is not 36.......Given a * b=ba−ba+ab, find (2*3)×(3*2).

User Dotcs
by
5.5k points

1 Answer

2 votes

Answer:

36

Explanation:

In the above question, we have been given a rule to follow

Given a * b = ba−ba+ab

We are to find (2*3)×(3*2)

Let simplify each bracket first

a * b = ba−ba+ab

2*3, a = 2, b = 3

2*3 = 3×2 - 3×2 + 2×3

= 6 - 6 + 6

= 6

a * b = ba−ba+ab

3*2, a = 3, b = 2

3*2 = 2×3 - 2×3 + 3×2

= 6 - 6 + 6

= 6

(2*3)×(3*2)

= 6 × 6

= 36

The answer is 36

User Hayato
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.